Synthesis of TiO2/Zeolite-A Composite for The Removal of Methylene Blue on Direct Sunlight - Yasokhi Fatkhasari; Nafiah Afuw Rouf; Wahida Annisa Ermadayanti; Randy Yusuf Kurniawan; Arseto Yekti Bagastyo (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Wastewater generated from textile industry contains azo dye, (e.g., methylene blue), which is inefficient to decompose by using biological processes, and requires long treatment time. TiO2 is the most widely used adsorbent for industrial applications and photocatalytic degradation of various azo dyes in textile wastewater. Its anatase is the most effective and widely used photocatalyst, however the wide band gap of TiO2 has limited its widespread application in industry since it needs to be excited by ultraviolet (UV) light. In order to overcome this issue, combination of adsorbent zeolite and TiO2 into the composite was used in this study so that TiO2 can adsorb methylene blue under direct sunlight. Composition of 1 g TiO2 and 1 g Zeolite composite was used in batch method to eliminate different methylene blue concentrations, i.e., 25; 50; 75; 100; 125; 150; 200; and 250 ppm by means of adsorption process under direct sunlight. The experimental result showed that addition of zeolite was able to considerably improve adsorption capacity of TiO2 on direct sunlight in the range of 97.2 – 99.3 % of methylene blue removal. The highest removal was observed in the case of lower concentrations of methylene blue, i.e., in the range of 25-50 ppm.